Vis-to-NIR electrochromism and bright-to-dark electrofluorochromism in a triazine and thiophene-based three-dimensional covalent polymer. Issue 12 (15th September 2022) - Halder, Sayan; Gupta, Neelam; Behere, Ravi Prakash; Kuila, Biplab Kumar; Chakraborty, Chanchal
Abstract : Two triazine and substituted thiophene-based donor–acceptor covalent polymeric frameworks are developed to exhibit the Vis-to-NIR electrochromism and bluish-green-to-quenched electrofluorochromism, simultaneously in a +1.8 to −0.9 V potential range. Abstract : Organic materials convey an excellent advantage in electrochromism as they exhibit moderate switching times and high colouration efficiency with a vivid colour range at a low potential window. Furthermore, conjugated polymeric frameworks (CPFs) are more superior in this regard due to their moderate surface area and porous nature. Herein, we designed and synthesized two triazine and substituted thiophene-based donor–acceptor (D–A) covalent polymeric frameworks (CPF1 and CPF2) to afford dual-performance reversible yellow-to-deep brown Vis-to-NIR electrochromism and bluish-green to quenched emission simultaneously in the +1.8 to −0.9 V potential range. The yellow-to-deep brown Vis-to-NIR electrochromism exhibited a fast switching time of 5.1 s for colouring and 8.6 s for bleaching with a high colouration efficiency of 163.7 cm 2 C −1 and high optical contrast of 36%. Both CPFs exhibited excellent cycling performances with a negligible loss of optical contrast over 150 cycles. The present study describes the potential scope of the D–A based porous CPF design strategy with organic molecular materials for providing dual-performance electrochromism and electrofluorochromism, which would be useful for the next-generation smart window technology.